Psychological impications of Fuko’s panoptikon in today Society - Slavković, Ana R. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2021)
The author of the paper explains Foucault’s basic ideas related to the use of panopticon in public institutions and society, with the aim to control and impose identity, in order to accomplish the interests of centres of power. The aim of this paper is to explain the ways in which panopticon operate in today’s society, through procedures of supervision and punishment. The author tries to apply Foucault’s initial ideas to today’s reality and explain the way in which the panopticon functions by forcing certain points of view in science which validity has not been empirically confirmed, forming a consumer society through imposed identities. The application of panopticon is based on the fear of people that they will be excluded from society and lose their positions, if they do not follow the roles imposed on them. They very easily give up their own identity for the sake of existential security and social status. The task of those scientists, psychologists and psychiatrists who have decided not to serve the interests of the centres of power is to be as clear and effective as possible, pointing out all the factors that lead to the formation of an unhealthy consumer society, as well as the mechanisms of their action.